2021
DOI: 10.34069/ai/2021.39.03.5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media on young web users’ psychological well-being during the COVID-19 pandemic progression

Abstract: Aim. The present study empirically investigates and theoretically substantiates the results of the impact of social media on young web-users’ psychological well-being during the forced self-isolation caused by the progression of the COVID-19 pandemic (N = 254). Materials and methods. Standardized valid psycho-diagnostic methods, the author’s questionnaire (A. Hudimova, 2021), correlation and factor analyses were used to identify young web users’ patterns of social media involvement during the forced self-isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…That was probably due to the greater exposure to Covid-19 related information online, although mindfulness skills buffered this adverse effect ( 49 ). A lack of cognitive control over the time spent on social media platforms likely exacerbated psychopathological symptoms and augmented a sense of isolation from social reality, fueling an obsessive cycle of social media usage patterns ( 59 ). Conversely, anxious participants reported using social media more often as a strategy to adapt to the current emergency and – to a lower extent – as a way to keep in touch with family and friends ( 60 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That was probably due to the greater exposure to Covid-19 related information online, although mindfulness skills buffered this adverse effect ( 49 ). A lack of cognitive control over the time spent on social media platforms likely exacerbated psychopathological symptoms and augmented a sense of isolation from social reality, fueling an obsessive cycle of social media usage patterns ( 59 ). Conversely, anxious participants reported using social media more often as a strategy to adapt to the current emergency and – to a lower extent – as a way to keep in touch with family and friends ( 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conclusions: Negative lifestyles of smoking and drinking, and being a woman, may be important risk factors for depressive symptoms, whereas exercise and having someone to consult about worries may be protective factors. Hudimova et al (59) The study proves that young people spend almost all day online due to the obsessive pattern of social media involvement and/or procrastination, which often provokes withdrawal syndrome upon the attempt to distract from them. The lack of controlled time spending on social media during self-isolation provokes an exacerbation of anxiety, apathy, depressed mood, and a sense of isolation from social reality.…”
Section: Id Author and Yearmentioning
confidence: 91%
“…-Marketing factors (e.g., product design, price, promotion, packaging, positioning, and distribution) [38]; -Personality characteristics (such as age, gender, education, and income) [39]; -Psychological drivers (purchase motives, product perception, and attitude to the product) [40]; -Situational framework (the physical environment at the time of purchase, the environment, and the time factor) [41]; -Social determinants (social status, reference groups, and family) [42]; -Cultural factors (religion, social class) [43]; -Intergenerational behavior [44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is worth noting that the situation with COVID-19 significantly changes the studied social reality (Khmiliar et al, 2020;Hudimova et al, 2021). At one time, the problem of mental states was the subject of research in the context of the transformation of stable properties into dominant mental states of personality (Izard, 2007;Prokhorov et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of the COVID-19 pandemic has created many problems for humanity and at the same time opened up new opportunities, forced to slow down the pace of life and rethink values (Khmiliar et al, 2020;Molchanova et al, 2020). Some modern studies have found that the lack of controlled spending of time by children in social networks during self-isolation exacerbates anxiety, apathy, encourages a sense of isolation from social reality (Hudimova et al, 2021).…”
Section: Science List Reviewmentioning
confidence: 99%